Kinerja Ratio Silika-Cat Dengan Metode Dipcoating Pada Permukaan Logam Untuk Penghambat Laju Korosi - Lisnawaty Simatupang; Rikson Siburian; Elfrida Ginting; Junifa Layla Sihombing; Herlinawati Herlinawati; Alex Suhendra Munte; Kristian Adinata Pratama Simatupang; Dea Gracella Siagian (Journal of Science and Applicative Technology, 2023)
Silica oxide (SiO2) is a chemical compound that can be obtained from the extraction of volcanic ash from Mount Sinabung. Silicon dioxide has the properties of high porosity, high mechanical strength, high thermal stability, large pore surface area, stable surface in acidic media so that it can be applied in the chemical coating field.This research aims to measurement of performance natural silica from volcanic ash of mount Sinabung Indonesia as additives to the paint to inhibit corrosion rate in metal surface. The addition of silica additives to the paint was carried out by dispersing (0; 0.5; 0.75; and 1) g with 10 mL of paint with each composition carried out for 60 minutes. Iron plate in sandpaper with 1500 grid and polished with bludru cloth using autosol metal polish, then coated with paint and a combination of silica-paint through the dipcoating method. The corrosion test was carried out on a corrosive solution of HCl 15% (v/v) and NaCl 3.5% (w/v). The corrosion rate using HCl 15% (v/v) showed C (0,286) mpy, SC1 (0,123) mpy, SC2 (0,149) mpy, SC3 (0,120) mpy. While at 3.5% (w/v) NaCl, namely C (0,282) mpy, SC1 (0,120) mpy, SC2 (0,142) mpy, SC3 (0,098) mpy. Inhibitor efficiency for various variations of silica composition in corrosive HCl 15%(v/v) solution, e.g., SC1 (56,9%), SC2 (47,9%), and SC3 (58,04%). The inhibitor efficiency at various compositions of silica in NaCl 3.5% (w/v) are SC1 (57,44%), SC2 (49%) dan SC3 (65,24%).